THE PHYSICAL FITNESS ACCORDING TO NUMBER OF STEPS IN ADULT AND OLDER WOMEN: A CROSS-SECTIONAL STUDY - da Silva Júnior, João Pedro; de Jesus Guimarães, Luís Fabiano; Rosa Bergamo, Raiany; Leandro Araújo, Timóteo; Keihan Rodrigues Matsudo, Victor; Mahecha Matsudo, Sandra Marcela (Journal of Health Care, 2023)
Introduction: The analysis of the number of steps has been associated with several variables related to the health of the elderly, in physical fitness, body composition, functional capacity and its reduction is related to several chronic non-communicable diseases. The reduction of the number of steps/day is associated with negative outcomes in body composition, disease development and risk of death from cancer. Objective: To compare muscular strength and functional capacity according to the number of steps of adult women practitioners of physical activities. Methods: participated in this study 159 adult women practitioners of physical activities aged 50 to 86 years (69,55Â±7.9 years old) Longitudinal aging project participants and physical fitness of São Caetano do Sul. The amount of steps was measured with the pedometer (Digiwalker 700SW 200 C), for seven consecutive days. The assessment of physical fitness was measured by the variables of upper and lower limbs strength and agility. Functional capacity was measured by the mobility and balance. For statistical analysis we used oneway ANOVA, followed by Bonferroni Post Hoc and the data was used nonparametric Kruskal-Wallis tests and Mann-Whitney. The number of steps was divided into tercil (1st tercil <5.618 steps/day; 2nd tercil 5619 - 9054 steps/day and 3rd tercil > 9055 steps/day). The significance level adopted was p<0.05. Results: It was found to be in upper tercil number of steps resulted in statistically significant differences in anthropometric variables: weight, BMI, waist circumference and hip circumference, in the variables of physical fitness: lower limb strength and agility and functional capacity in the variables of General mobility and locomotion. Conclusion: Women who have a greater number of steps achieved a best anthropometric profile of neuromotor, and functional.